MODEL PENGEMBANGAN KELINCAHAN GERAK DALAM PENJASORKES MELALUI PENDEKATAN LINGKUNGAN PERSAWAHAN (Department of Physical Education, Sport, Health and Recreation, 2013)
This study aims to determine the model of development in the movement agility Penjasorkes environmentalapproach through rice fields. This development model is to approach learning environment to improve agilitymotion paddy children include: 1) research and gathering information early, 2) preliminary research, 3)planning, 4) development of initial product formats; 5) manufacturing model of development; 6) initial producttrials; 7) revision of the initial product; 8) field trials; 9) revision of the final product; 10) model of learningoutcomes and 11) dissemination and implementation. The results with the model of development can be seenthat most of the students have an excellent motion agility. This is consistent with one of the objectives ofphysical education is to increase the agility of motion student. With the agility of motion enabled students toperform learning tasks and activities outside of school as well. The conclusions show that the motion agilityPenjasorkes through paddy environmental approach can improve the learning process in the student categoryPenjasorkes well. This research suggestion that this product can be used for learning agility of motion; penjasteachers are expected to create another model of learning development to increase agility movements learners;teachers who have difficulty in increasing the agility of motion, this product can be used as a solution.